THE INFLUENCE OF DIFFERENT TIME OF APPLICATION AND DOSES OF GRAMAXON ON BINDWEED CONTROL - S . H . Anter (Mesopotamia Journal of Agriculture)
Pots experiment was carrid out at Salah aldeen prov. in 2006 summer growing season to investigate the effect of herbicide doses (150, 300, 450 cm3a.i/ha) application time (15 , 25 , 30 days intervals ) and frequent application ( without application , one , two , three time of application ) on growth of bind weed . Data wrer collected at 25th October . CRD design with three replicates was used as a factorial experiment. Unsignificant result had seen on all growth characteristic of plant with the different time of herbicide application . While the third dose of herbicide was significantly superior than other doses . The more frequency of herbicide application had significant effect on reducing plant length , dry weight , number of buds , and number of branch . The interaction two or three time of application at dose 450cm3 a.i/ ha with every 15 , 25 or 35 days duration had markedly effect on plant growth which all plants was control